Serum C3 and Renal Outcome in Patients with Primary Focal Segmental Glomerulosclerosis - Jian Liu (Nature Portfolio, 2017)
Abstract The role of complement (C) in the pathogenesis or progression of focal segmental glomerulosclerosis (FSGS) is uncertain. The present study assessed the relationship between serum C3, the baseline characteristics, and the progression of FSGS in the cohort and identified the clinical implications of serum C3 levels in patients with FSGS. Compared to the patients with C3 ≥ 85 mg/dL (N = 474), those with C3 < 85 mg/dL (N = 117) presented a higher level of serum creatinine, lower levels of eGFR, hemoglobin, proteinuria, triglyceride, cholesterol, IgA, as well as, severe tubulointerstitial injury (TI). Of the 221 patients with a mean follow-up of 53.3 months, the risk of reaching end-stage renal disease (ESRD) was significantly higher in patients with low serum C3 level (p < 0.001). An additional 40 patients with primary FSGS revealed a significant correlation between MAC and AP (p = 0.003), MAC and serum C3 (p = 0.018), and AP and serum C3 (p = 0.028). Compared to patients with none-to-mild TI, those with moderate-to-severe TI exhibited a lower level of serum C3 and AP, and a higher level of serum MAC. In conclusion, complement activation occurring in patients with FSGS is associated with clinical and histological severities. Low serum C3 was an independent risk factor for poor renal outcome in patients with FSGS.